Ethnomedicinal Survey of Plants Used In Treating Sexually Transmitted Diseases in Abia State, Nigeria - Nduche, M. U; Okwulehie, I. C (Review of Plant Studies, 2014)
The prevalence of sexually transmitted diseases in Nigeria is still high. In this study, an ethno medicinal survey was conducted to record the different plant families, species and plants parts used for the treatment of sexually transmitted diseases in Abia State of Nigeria. The result revealed that a total of 62 plant species in 48 genera from 44 families mostly the Euphorbiaceae, Fabaceae, Asteraceae, Rutaceae, and Malvaceae were used to treat diseases such as gonorrhoea, syphilis, trichonomiasis, chlamydia, urethritis, and to suppress the replication of HIV. The most plant parts used were leaves (32.5%), stem bark (23.75%) and root (20%). Other parts used included the fruits (7.5%), the seeds (3.75%) and the aerial parts (12.5%). More research is needed to extract and isolate the active chemical compounds under sound hygienic condition and study their mode of function.